Seriosa Dalam Konteks Liturgi Gereja Katolik: Kajian Implementasi Teknik Vokal Klasik (Seriosa) Dalam Peribadatan - Egidius Bagas Pinasthiko Aji; Helena Evelin Limbong; Selamat Triadil Saragih (Institut Agama Kristen Negeri Palangka Raya, 2026)
The development of contemporary church music often shifts attention away from the quality of liturgical vocals, particularly in the ministry of singing carried out by cantors/psalmists and choirs who lead the congregation. Yet, excellent vocal technique is a crucial element for leading the congregation in prayer and conveying the liturgical message with reverence. This research aims to examine the implementation of classical (seriosa) vocal technique within the context of worship, focusing on its function in enhancing the musical quality and spirituality of the liturgy. The research method used is descriptive qualitative with a library research approach. This approach was chosen because the study focuses on the exploration, analysis, and conceptual synthesis needed to answer theoretical-explanatory research questions regarding the integration of seriosa vocal technique into the liturgical realm. The research results indicate that the application of seriosa principles (such as diaphragmatic breathing, voice formation, articulation, and clear phrasing) significantly improves the clarity, projection, stability, and prayerful quality of liturgical singing. However, its implementation faces challenges such as the lack of specialized vocal training for liturgical ministers and the need to adapt the technique to remain flexible and not overly operatic. The research conclusion underscores that seriosa vocal technique is not merely an artistic achievement but an effective pastoral tool for supporting the congregation's actuosa participatio. The implication is the necessity of integrating contextual seriosa-based vocal training into the formation of future priests, religious figures, and leaders of liturgical music.